Problem:
Let's denote the above equation like this:
x-3y = -12 EQUATION 1
2x + y = 11 EQUATION 2
Solve x from equation 2:
2x = 11-y
this is equivalent to say (EQUATION 3)

Now, replace the variable x in equation 1, that is:

this is equivalent to say:

Putting together similar terms on different sides of the equation we get:

this is equivalent to:

this is equivalent to:

this is equivalent to:

solve for y:

then, we can conclude that y = 5. But, from lines back we know that x is equal to (EQUATION 3):

Replacing y in the previous equation, we obtain

then, we can conclude that:
X = 3
Y = 5